(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
Government especially in the environment of the district. The methods used in this study a greater emphasis on qualitative research methods. Where this method does not intend to look for a causal result of anything but trying to understand the situation and specific background as it is. The results showed the company that wants to progress and grow of course require supervision, because any trace of the surveillance activity carried out at the course in an enterprise will not be achieved as expected. One of the supervisory efforts undertaken within the Organization of the district is the oversight on the territory of the District of the Organization in the field of Kembu necessarily requires the implementation of supervision. Supervisory efforts is one of the tools of control that is exercised against his leadership. Key words: Role, head of Supervision